Clinical Performance and Concurrent Validity of the Adult Spinal Deformity Surgical Decision-making Score. Issue 14 (15th July 2020) - Fujishiro, Takashi; Boissière, Louis; Cawley, Derek Thomas; Larrieu, Daniel; Gille, Olivier; Vital, Jean-Marc; Pellisé, Ferran; Pérez-Grueso, Francisco Javier Sanchez; Kleinstück, Frank; Acaroglu, Emre; Alanay, Ahmet; Obeid, Ibrahim
Abstract : Study Design: Multicenter, retrospective study. Objective: The aim of this study was to examine the performance and concurrent validity of the adult spinal deformity surgical decision-making (ASD-SDM) score compared to decision-making factors in the ASD population. Summary of Background Data: The ASD-SDM score, which has been recently proposed, is a scoring system to guide the selection of treatment modality for the ASD population. To secure the justification for its clinical use, it is necessary to verify its clinical performance and concurrent validity. Methods: A multicenter prospective ASD database was retrospectively reviewed. The data were analyzed separately in younger (⩽40 years) and older (≥41 years) age groups. The discriminating capacity of the ASD-SDM score in cases who selected surgical and nonsurgical management was compared using area under the receiver operator characteristic curves (AUROC). Concurrent validity was examined using Spearman correlation coefficients, comparing factors that are reported to be associated with the decision-making process for ASD, including baseline symptomatology, health-related quality of life measures, and the severity of radiographic spinal deformity. Results: There were 338 patients (mean age: 26.6 years; 80.8% female; 129 surgical and 209 nonsurgical) in the younger age group and 750 patients (mean age: 63.5 years; 84.3% female; 410 surgical and 340 nonsurgical) in the older age group. In both younger and older patients, the ASD-SDM score showed a significantly higher performance for discriminating the surgical and nonsurgical cases (AUROC: 0.767, standard error [SE]: 0.026, P < 0.001, 95% confidence interval [CI]: 0.712–0.813; AUROC: 0.781, SE: 0.017, P < 0.001, 95% CI: 0.747–0.812, respectively) compared to the decision-making factors analyzed. In addition, the ASD-SDM showed significant correlations with multiple decision-making factors. Conclusion: The ASD-SDM score alone can effectively grade the indication for surgical management whilst considering multiple decision-making factors. Level of Evidence: 3 Abstract : This study demonstrated that the adult spinal deformity decision-making (ASD-SDM) score, which was a recently proposed scoring system to guide the selection of treatment modality for the ASD population, could effectively grade the indication for surgical management while considering multiple decision-making factors.